Implementation of Augmented Reality and Virtual Reality Technology to Improve Distance Learning - Casmat, Memet; Ali Muralitharan (LPPM Universitas Terbuka, 2025)
This study concludes that the implementation of Augmented Reality (AR) and Virtual Reality (VR) technology has significant potential to improve the quality of distance learning in both Indonesia and Singapore in the post–Covid-19 era. The application of AR and VR enables learners to access more interactive, immersive, and flexible learning experiences, overcoming geographical limitations and diverse demographic challenges, especially in Indonesia as an archipelago country. In Singapore, these technologies support efficient and innovative learning in line with its advanced industrial and educational environment. Through qualitative analysis involving observations, interviews, and document studies with more than 30 respondents from Universitas Terbuka and the National University of Singapore, the findings reveal that AR and VR enhance students' knowledge, skills, and learning engagement. Students also demonstrated positive attitudes toward the integration of these technologies into distance education. Therefore, this study strongly recommends the wider adoption of AR and VR in distance learning systems as an effective strategy to improve learning quality, increase accessibility, and support sustainable educational development in both countries.